Legal Review of Government Policies in Handling Agrarian Conflicts - Judijanto , Loso (Journal of Scientific Insights, 2025)
This research examines the complex landscape of agrarian conflicts and the legal frameworks employed by governments worldwide to address these disputes. Agrarian conflicts remain persistent challenges for many nations, often stemming from historical injustices, overlapping land claims, resource competition, and inadequate policy responses. Through qualitative descriptive research utilizing a library research approach, this study analyzes existing legal frameworks, policy implementation strategies, and resolution mechanisms across various jurisdictions. The research identifies critical gaps in current governance structures, highlighting the need for more inclusive, transparent, and culturally sensitive approaches to agrarian conflict resolution. The study concludes that effective management of agrarian conflicts requires a comprehensive legal framework that balances development objectives with the protection of vulnerable communities' rights, while emphasizing participatory approaches to policy formulation and implementation. This research contributes to scholarly understanding of how legal systems can better address the multifaceted nature of agrarian conflicts and proposes policy reforms to enhance conflict resolution outcomes.